Current state of methods for low–dense constructional composite materials producing (overview) - Shcherbakova, E.P.; Prokhorova, A.D.; Karpenko, A.V.; Yanko, T.B. (Вопросы атомной науки и техники, 2020)
The analysis of existing methods for imparting a porous structure to structural composite materials is carried out. In particular, the introduction and subsequent removal of the filler, the addition of foaming agents or separately prepared foam to the suspension, as well as gas formation. Discloses a method of introducing into the material of the hollow microspheres, which finds use in the development of thermal barrier composites. The introduction and subsequent carbonization of additives is considered. A method for producing highly porous carbon-graphite materials with a uniformly distributed pore structure using isostatic pressing with pyrocarbon in the form of a binder is considered. Describes the receipt as highly porous carbon materials of foam coke based on carbon microspheres, carbon materials based on fibers, pressed carbon black, porous pyrocarbon and related materials, as well as porous glassy carbon.